Simultaneously enhancing the mechanical properties and corrosion resistance in a selective laser melting AZ91 magnesium alloy by hot rolling and subsequent annealing - Li Wang; Shouxin Xia; Qinghang Wang; Xu Qin; Bin Jiang (Journal of Materials Research and Technology)
The influence of post-processing hot rolling followed by annealing (RA treatment) on the microstructure and mechanical/corrosion properties of a selective laser melting (SLM) AZ91 magnesium (Mg) alloy was studied. The findings demonstrated that the RA treatment eliminated defects, reduced the Mg17Al12 phase fraction, refined grain and phase sizes, and induced a strong basal texture. The RA sample exhibited a remarkable increase in tensile yield strength (∼300 MPa), along with an acceptable elongation (∼9.0 %). The corrosion resistance of the SLM sample was significantly ameliorated, reflected by decreasing the corrosion rate from 31.6 to 7.2 mm/y. The basal-oriented grains, along with reduced defects and fine Mg17Al12 particles, played crucial roles in mitigating pitting and micro-galvanic corrosion, effectively acting as barriers to slow down the corrosion process. Therefore, the RA treatment represents a promising strategy for developing high-performance, corrosion-resistant SLM Mg alloys.